2009
DOI: 10.1097/mao.0b013e3181b1212e
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With Congenital Cytomegalovirus Infection

Abstract: Long-term results of the language perception and production after CI was satisfactory in Japanese children with congenital CMV-related deafness compared with in subjects deafened by other causes. CMV alone, as a cause of deafness, is not likely a contraindication for CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 26 publications
1
43
1
2
Order By: Relevance
“…There are no publications to our knowledge that report the incidence of CMV infections in SSD patients. In children with bilateral congenital deafness, CMV infection is reported to be a common cause by Deltenre and Van Maldergem [2013] and Yoshida et al [2009]. Intrauterine CMV infection is estimated to affect approximately 0.5-2.5% of all live births [Hagay et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no publications to our knowledge that report the incidence of CMV infections in SSD patients. In children with bilateral congenital deafness, CMV infection is reported to be a common cause by Deltenre and Van Maldergem [2013] and Yoshida et al [2009]. Intrauterine CMV infection is estimated to affect approximately 0.5-2.5% of all live births [Hagay et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another reason for the poor audiological results of our congenitally deaf children might be the congenital CMV infection, since other authors, e.g. Yoshida et al [2009], reported inferior outcomes of CI surgery in bilaterally deaf children due to congenital CMV infection compared to children with non-CMV-related deafness. In agreement, Viccaro et al [2012] described long-term results for CI surgery in 6 children with congenital CMV-related deafness; only 2 of them showed appropriate use of grammar and syntax, the other 4 used only single words.…”
mentioning
confidence: 92%
“…This outcome might be related to central nervous system involvement since no association between duration of deafness, age at implant and speech outcomes was evident in our study group. Yoshida et al [2009] claim that CMV children without cognitive delay manage to bridge the gap with their non-CMV peers over a 1-year follow-up. However, in our long-term study we showed how both symptomatic and asymptomatic CMV implantees still underperformed both in speech perception and language development compared to their non-CMV peers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also important to remember that CMV children have poor attention control and are considered more susceptible to later complications such as learning difficulties. Hence, careful observation is required on clinical course after cochlear implantation [Yoshida et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…One year after CI, language perception and production showed similarly good progress for both the CMV-and non-CMV-related hearing loss groups. (Yoshida et al 2009) Prompt detection and management of late-onset hearing loss in early childhood have also been shown to improve language development, including a benefit from early fitting with cochlear implants. (Stacey et al 2006;Nicholas and Geers 2007) For example, one study demonstrated that being implanted within 12 months of hearing loss onset was associated with significantly better language outcomes.…”
Section: Newborn Screening Criteria and Congenital CMVmentioning
confidence: 99%